Lafẓ “Al-Auliyā'” baina an-Naṣṣ wa al-Wāqi‘: Dirāsah Dalāliyyah - Hatta Raharja (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
This article examines the condition of Jakarta's residents in late 2016 and early 2017. Some Muslims in Jakarta were able to mobilize a movement they dubbed